2008
DOI: 10.1210/en.2008-0111
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Osteoclastogenesis by Fatty Acids

Abstract: Clinical studies have shown that total body fat mass is related to both bone density and fracture risk and that fat ingestion reduces bone turnover. These effects are at least partially mediated by endocrine mechanisms, but it is possible that lipids might act directly on bone. We assessed the effects of broad fractions of milk lipids in osteoblasts, bone marrow, and neonatal mouse calvariae. Several milk fractions and their hydrolysates inhibited osteoclastogenesis in bone marrow cultures, so we assessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 21 publications
5
94
2
Order By: Relevance
“…Contrary to our results, inhibition or no signifi cant effect of OC formation by SFA in murine macrophage cell line, RAW264.7 cells, has been reported ( 26,27 ). However, they did not distinguish the effect of SFA at specifi c stage.…”
Section: Mip-1 ␣ Generated By Mature Oc In Response To Sfa Is Responscontrasting
confidence: 99%
“…Contrary to our results, inhibition or no signifi cant effect of OC formation by SFA in murine macrophage cell line, RAW264.7 cells, has been reported ( 26,27 ). However, they did not distinguish the effect of SFA at specifi c stage.…”
Section: Mip-1 ␣ Generated By Mature Oc In Response To Sfa Is Responscontrasting
confidence: 99%
“…In contrast to the work reporting effects of LCPUFAs on bone cells, Cornish et al [104] recently reported an effect of saturated fatty acids on osteoclastogenesis. They studied several short and medium chain fatty acids and stearic (C18:0) and palmitic acid (C16:0) exhibited a significant inhibitory effect on osteoclastogenesis.…”
Section: Effects Of Polyunsaturated Fatty Acids On Osteoclastogenesismentioning
confidence: 84%
“…Cornish et al (24) showed that RAW264.7 cells express both GPR120 and GPR40 at the mRNA levels and hypothesized a potential role of these receptors in the effects of saturated fatty acids on osteoclastogenesis. In addition, Oh et al (23) recently demonstrated that GPR120 was responsible for mediating docosahexaenoic acid anti-inflammatory properties in a macrophage …”
Section: Discussionmentioning
confidence: 99%
“…As bone tissues share common precursor cells with the hematopoietic lineage, GPR40 expression was investigated in bone cells (24,25). Indirect evidence in support for a role of GPR40 in fatty acid stimulation of bone formation was provided by Cornish et al, who observed that GPR40 is expressed in osteoclasts and that a GPR40 agonist mimics fatty acid inhibition of osteoclastogenesis (24). Mieczkowska et al recently confirmed the expression of GPR40 in bone cells and observed that down-regulation of GPR40 by RNA interference protects from thiazolidinedione-induced osteocyte apoptosis (25).…”
mentioning
confidence: 99%